2019
DOI: 10.1111/jiec.12838
|View full text |Cite
|
Sign up to set email alerts
|

Environmental analysis of producing biochar and energy recovery from pulp and paper mill biosludge

Abstract: Sweden is one of the largest exporters of pulp and paper products in the world. It follows that huge quantities of sludge rich in carbonaceous organic material and containing heavy metals are generated. This paper carried out a comparative environmental analysis of three different technologies, which can be adopted to produce biochar and recover energy from the biosludge, using landfilling as the reference case. These three thermochemical biosludge management systems—using incineration, pyrolysis, and hydrothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…A consequence of the strong interrelationships between the various aspects of AD is the advances so far made in the optimization of the technology such that research on only one aspect may not be technically reliable hence the need for studies to be conducted on other aspects of the technology. Digester design innovations, recycling of digested slurry, the use of other non-biological conductive materials like biochar (a solid product of thermal decomposition of biomass) to improve AD and digestate as well as the ability to co-digest different feedstocks are some of the recent advances made in the AD technology [111][112][113][114][115][116][117][118][119]. The use of composite materials such as magnetic fly ash (Fe 3 O 4 /FA) for pretreatment of mainly livestock manure used as feedstock in AD processes [78] are among some of the other recent advances made in optimization of AD systems but the economic viability of this pretreatment method is yet to be determined.…”
Section: Recent Advances In the Ad Technologymentioning
confidence: 99%
“…A consequence of the strong interrelationships between the various aspects of AD is the advances so far made in the optimization of the technology such that research on only one aspect may not be technically reliable hence the need for studies to be conducted on other aspects of the technology. Digester design innovations, recycling of digested slurry, the use of other non-biological conductive materials like biochar (a solid product of thermal decomposition of biomass) to improve AD and digestate as well as the ability to co-digest different feedstocks are some of the recent advances made in the AD technology [111][112][113][114][115][116][117][118][119]. The use of composite materials such as magnetic fly ash (Fe 3 O 4 /FA) for pretreatment of mainly livestock manure used as feedstock in AD processes [78] are among some of the other recent advances made in optimization of AD systems but the economic viability of this pretreatment method is yet to be determined.…”
Section: Recent Advances In the Ad Technologymentioning
confidence: 99%
“…Similarly, Liu et al [56] found that exchangeable and reducible fraction of heavy metals in sewage sludge decreased by hydrothermal carbonization. The immobilized heavy metals in hydrochar considerably reduce the terrestrial ecotoxicity [24] and aquatic ecotoxicity impacts [25] of soil application of biochar.…”
Section: Nutrient and Heavy Metal Contentsmentioning
confidence: 99%
“…Moreover, peat use reduction due to replacement with hydrochar will result in less peat extraction and, therefore, will decrease the associated environmental impacts. Results of our previous studies showed that pyrochar and hydrochar production from paper mill sludge can significantly increase the environmental performance of sludge management and contribute to sustainable forest ecosystems [24,25]. Hydrochar-amended substrates can contribute to climate change mitigation with carbon sequestration as part of the normal reforestation.…”
Section: Environmental and Economic Implications Of Using Hydrocharmentioning
confidence: 99%
See 1 more Smart Citation
“…PPBS consists of lignocellulose material from the pulp and paper process [12], heavy metals [13,14], as well as bacterial cells from the wastewater treatment. The composition of PPBS varies depending on the paper mill process and wastewater treatment, but typically it contains crude protein 1.5-8.3%, fat 0.3-3.3%, dry substance (DS) 10-30%, lignin 17-40% DS, nitrogen 18,000-84,000 mg/kg DS, phosphorus 1700-21,000 mg/kg DS, potassium 200-4600 mg/kg DS, and ash (27% DS) [13,15].…”
Section: Introductionmentioning
confidence: 99%